PENGARUH EFEKTIVITAS AMPLIFIED E-WOM DI INSTAGRAM TERHADAP SIGNIFIKANSI JUMLAH KUNJUNGAN E-COMMERCE DALAM EVENT PROMO TANGGAL CANTIK - Fajrina Amalia Hasibuan, (2023)
Indonesia is a country with the highest e-commerce users in the world based on the results of a survey conducted in 2021. The large number of e-commerce that have sprung up has made competition even tougher in acquiring consumers and gaining excellence in achieving transactions. Tokopedia is one of the e-commerce companies that carries out marketing strategies using social media Instagram. The purpose of this study was to examine the effect of the effectiveness of amplified e-WOM on the number of visits on the Tokopedia application using Persuasive Communication Theory and the AISAS model as the basis for the assumptions of this study. This research is an explanatory qualitative study using a survey method. As many as 180 respondents are followers of the Instagram account @tokopedia. The results showed that there was a moderate relationship between the effectiveness of amplified e-WOM and the significance of the number of application visits of 0.487. While the results of the test for the coefficient of determination stated that there was an effect caused by the effectiveness of amplified e-WOM of 23.8% on the number of application visits and for each additional 1% of the effectiveness of amplified e-WOM, the number of application visits would increase by 0.843. The conclusion of the study based on the results of hypothesis testing found t count > t table, which is equal to 7.446, it can be concluded that there is a moderate influence between the effectiveness of amplified e-WOM on Instagram @tokopedia during the visit of the Tokopedia application during promo event.